The Plant-Derived Naphthoquinone Droserone Inhibits In Vitro Measles Virus Infection - Lieberherr, Christina; Zhang, Guoliang; Grafen, Anika; Singethan, Katrin; Kendl, Sabine; Vogt, Valentin; Maier, Jonathan; Bringmann, Gerhard; Schneider-Schaulies, Jürgen (Planta Medica, 2017)
The naphthoquinone droserone (1) is a natural product occurring in dicotyledonous plants. We have now observed that the addition of 1 during infection of tissue culture cells with measles virus considerably reduced the infection. Interestingly, the infection was inhibited only when droserone (1) was added during virus entry, but not when added to the cells prior to virus uptake or after virus uptake. These findings suggest that 1 interacts with viral particles to reduce infectivity. The formation of progeny measles virus particles was inhibited to 50 % by droserone (1) at a concentration (IC50) of approximately 2 µM with a half-maximal cytotoxicity (CC50) of about 60 µM for Vero cells. Other tested naphthoquinone derivatives, among them the likewise natural plumbagin (2), but also synthetic analogs, were either more cytotoxic or not as effective as 1. Thus, our data do not support the development of naphthoquinone derivatives into antiviral compounds, but suggest that they may be interesting research tools to study measles virus entry into cells.
Keywords: Dioncophyllaceae; Ancistrocladaceae; Triphyophyllum peltatum; droserone; naphthoquinones; measles virus inhibition